Frank sign as a marker of atherosclerosis - Luís Flores; Fernando Friões (Sociedade Galega de Medicina Interna, 2020)
Bilateral diagonal earlobe crease, also known as Frank sign, was initially described in association with coronary artery disease, there after it has been associated with atherosclerotic disease in other territories. We present the image of a patient with that sign and diffuse atherosclerosis disease.